Investigation of the effectiveness of body protectors used in karate kumite competitions - Erdemir, O.; Soykan, A. (International Journal of Applied Exercise Physiology, 2020)
This study aimed to examine the effectiveness of impact protection of body protectors, which are mandatory to be used in Karate Kumite competitions. The research was conducted on three different body protectors approved by the World Karate Federation (WKF)for use in official competitions. Testing was performed both with high-and low-energy impacts applied on the body protectors using a specially designed setup, and the average values of acceleration, force, pressure, impulse, and impact area were calculated. The three body protectors differed in their ability to suspend both low-and high-energy impacts (p<0.05). For low-energy impacts, the three different brands of body protectors (A, B and C respectively) decreased impact acceleration by 4.98% (A), 5.37% (B), 7.23% (C); impact force by 22.56% (A), 30.91% (B), 54.71% (C); impact pressure by 19.10% (A), 26.86% (B), 20.57% (C), and impact impulse by 37.07% (A), 41.31% (B), 66.02% (C). For high-energy impacts, acceleration decreased by 5.34% (A), 6.75% (B), 11.23% (C); impact force by 27.81% (A), 5.15% (B), 25.33% (C); pressure by 28.52% (A), 14.47% (B), 22,56% (C); and impulse by 28.67% (A), 5.68% (B), 20.20% (C). In conclusion, the significant differences between the different body protectors may result in the ineffective suspension of applied impact during the competition, especially during high energy contacts. The manufactures have to provide sport-specific solutions for the nonlinear and inadequate suspension behavior of these body protectors.